PROFIL KEMAMPUAN PEMBUKTIAN MATEMATIKA MENGGUNAKAN METODE INDUKSI MATEMATIK SISWA KELAS XI SMAN 5 MODEL PALU DITINJAU DARI GAYA BELAJAR - Jusmawati, Jusmawati; Paloloang, Baharuddin; Rochaminah, Sutji; Hasbi, Muh. (Universitas Tadulako, 2025)
This study aims to describe the ability of mathematical proof using mathematical induction method of students who have visual, auditorial and kinesthetic learning styles. The subjects of this research are 3 students who are representatives of each learning style, namely 1 student who has a visual learning style, 1 student who has an auditory learning style and 1 student who has a kinesthetic learning style. This research is a descriptive research that describes students' mathematical proof ability using mathematical induction method adapted to visual, auditory and kinesthetic learning styles. The results showed that students with visual and auditorial learning styles were able to perform mathematical proof using mathematical induction in the basic steps and induction steps but only up to the correct assumption for n = k while students with kinesthetic learning styles could not apply the principle of mathematical induction correctly, in th basic steps students substituted n = 1 and n = 2 into the statement and ther were error in arithmetic operations.